A comparative study of the open versus closed method of pneumoperitoneum creation in laparoscopic surgery - Vaishnani, Bhavesh V.; Kachhadiya, Kapil R.; Chauhan, Mohit R. (International Surgery Journal, 2021)
Background: The main challenge facing the laparoscopic surgery is the primary abdominal access, as it is usually a blind procedure and associated with many complications including life threading vascular and visceral injuries. Techniques for the creation of pneumoperitoneum in laparoscopy include the standard technique of insufflation after insertion of the Veress needle (closed method), open laparoscopy (Hasson technique) and many others. Methods: This is observational study conducted in the department of General surgery, PDUMC, Rajkot from September 2018 to September 2020 comprising of 100 cases, 50 cases from each methods. The patients admitted in our department for Laparoscopic surgery was taken up for the study. The Purpose of our study is to assess the practicality of both methods in creation of pneumoperitoneum and to compare both methods with regards to ease of performance and incidence of complications. Results: Average size of incision (p=-5.426) is more in open method, hence more incidence of minor complications like multiple attempts, gas leak at port site and port site bleeding in open method while less duration for creating pneumoperitoneum (p=0) as compared to closed method. While there is no major complications in either groups. Conclusions: Open technique is as good as closed technique, and is good alternative to closed technique.